2021
DOI: 10.1177/20417314211019238
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional porous scaffolds derived from collagen, elastin and fibrin proteins orchestrate adipose tissue regeneration

Abstract: Current gold standard to treat soft tissue injuries caused by trauma and pathological condition are autografts and off the shelf fillers, but they have inherent weaknesses like donor site morbidity, immuno-compatibility and graft failure. To overcome these limitations, tissue-engineered polymers are seeded with stem cells to improve the potential to restore tissue function. However, their interaction with native tissue is poorly understood so far. To study these interactions and improve outcomes, we have fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Specific staining revealed that the cells were positive for CD29, CD44, CD73, CD90, CD105 and CD166 and negative for CD14, CD31, CD34 and CD45 (adipose-derived mesenchymal stem cells; normal, human (ATCC PCS-500-011)). The cell line has been used to date for various research applications, including adipose tissue regeneration [ 21 ], osteointegration in bioactive coatings [ 22 ], chondrogenesis [ 23 ] and neurogenesis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific staining revealed that the cells were positive for CD29, CD44, CD73, CD90, CD105 and CD166 and negative for CD14, CD31, CD34 and CD45 (adipose-derived mesenchymal stem cells; normal, human (ATCC PCS-500-011)). The cell line has been used to date for various research applications, including adipose tissue regeneration [ 21 ], osteointegration in bioactive coatings [ 22 ], chondrogenesis [ 23 ] and neurogenesis [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lack of crosslinkers also allow the CC scaffolds to have lower water angle as compared with the genipin‐crosslinked CC scaffolds as reported by another study 32 . Increase in hydrophilicity due to addition of fibrinogen in CCF scaffold was observed and therefore high angiogenic and wound healing potential may be obtained 33 …”
Section: Resultsmentioning
confidence: 84%
“…32 Increase in hydrophilicity due to addition of fibrinogen in CCF scaffold was observed and therefore high angiogenic and wound healing potential may be obtained. 33 CD spectroscopy: CD spectra of CCF scaffolds was acquired to characterize the interactions between different components. chitosan/alginate composites.…”
Section: Healing Progression Assessment In Vivomentioning
confidence: 99%
“…For its high biocompatibility and bioactivity, the natural polymer collagen was selected for scaffold fabrication in this research. Collagen is the most abundant structural protein in the connective tissues, and its homology across species provides low antigenicity and high biocompatibility [ 60 , 61 ]; in humans, collagen represents one-third of the total protein content in the body [ 62 ]. Over the last two decades, four major scaffolding approaches for TE have evolved: pre-made porous scaffolds, decellularized extracellular matrix (ECM), cell sheets with self-secreted ECM, and cell encapsulation in a self-assembled hydrogel matrix [ 63 ].…”
Section: Introductionmentioning
confidence: 99%